1997
DOI: 10.1097/00001888-199712000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment at one school of studentsʼ abilities and confidence in diabetic patientsʼ education

Abstract: Although they were clearly interested in diabetic patients' education, the students did not feel confident in providing it, nor did they have the cognitive competence to do so. Medical schools have a responsibility to students and to their patients to formally address the issues of patient education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Orleans et al (1980) showed that patients relate more favorably to learners who believe they have improved their clinical skills over the course of a rotation. Still, McCord et al (1997) found that confident students assigned to teach a topic were no more likely to have accurate information than less confident students. Barr and Graffeo (2016) showed that students who had performed more clinical procedures were more confident than their peers.…”
Section: Discussionmentioning
confidence: 94%
“…Orleans et al (1980) showed that patients relate more favorably to learners who believe they have improved their clinical skills over the course of a rotation. Still, McCord et al (1997) found that confident students assigned to teach a topic were no more likely to have accurate information than less confident students. Barr and Graffeo (2016) showed that students who had performed more clinical procedures were more confident than their peers.…”
Section: Discussionmentioning
confidence: 94%
“…Students’ lack of confidence and minimal formal training in patient counseling have been described as factors that can influence their ability to counsel patients and close an encounter in a more effective manner. 8 10 Additionally, SP feedback suggests that this situation occurs because students end the encounter with a promise to return after talking to the team about the patient as opposed to making a plan or counseling the patient themselves. Further research is needed to better understand the barriers students face while closing patient encounters, counseling patients, and providing next steps for evaluation and management.…”
Section: Discussionmentioning
confidence: 99%